Transfer Characteristics of the Nonlinear Parity-Time-Symmetric Wireless Power Transfer System at Detuning - Changsheng Li (Energies, 2020)
The nonlinear parity-time-symmetric wireless power transfer (NPTS-WPT) system is more robust against transfer distance than the traditional WPT system. Current studies mainly focus on the situation in which the transmitter (Tx) and the receiver (Rx) are completely matched. Our study focuses on the transfer characteristics of the NPTS-WPT system under detuning between the Tx and the Rx. First, the mathematical model of the detuned system is established, and then the model is solved using Shengjin’s formula. Then, the exact analytical solutions for the operating frequency, the amplification factor of the operational amplifier (OP Amp) and the transfer efficiency at detuning are obtained. It was noted, for the first time, that even though the Tx and the Rx were completely matched, a frequency jump could occur when the distance between the Tx and Rx coils slowly changed. Our study found that when the degree of detuning of the system changed, the operating frequency of the system could jump. By investigating the amplification factor of the OP Amp, the reason for the frequency jump when the system was detuned was explained. Our study also revealed that detuning did not imply a decreased transfer efficiency, and the over-detuning can improve the transfer efficiency sometimes. Finally, an experimental system was constructed, and the correctness of the theory was validated using the experimental system.